Strategi Pengembangan Usaha Peternakan Sapi Potong Di Kecamatan Perbaungan, Sumatera Utara - Lastri Lastri; Tri Anisa; Siti Hardiyanti Munthe; Nadzira Putri Syifa; Kiagus Muhammad Zain Basriwijaya (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
In this study to see how small to medium-scale farmers face problems when developing beef cattle farming businesses in Perbaungan District, North Sumatra. The research utilised a descriptive survey to collect data through field observations, structured interviews and desk research. The research involved beef cattle farmers from various business scales. Livestock production, feed use and capital constraints were included in the quantitative and descriptive analyses.The results showed that low-quality feed, capital availability and technical knowledge affected livestock productivity in the area. Large-scale farmers use commercial feed to get better results, while small-scale farmers rely more on natural feed. Improved access to high-quality feed, technical training and low-interest business credit are some of the development plans. Thus, to achieve sustainability of the sector, beef cattle enterprise development requires a holistic approach with government support, continuous training and cooperation with relevant institutions.